1994
DOI: 10.2105/ajph.84.4.599
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recall on estimating annual nonfatal injury rates for children and adolescents.

Abstract: OBJECTIVES. This study used a recent national population survey on childhood and adolescent non-fatal injuries to investigate the effects of recall bias on estimating annual injury rates. Strategies to adjust for recall bias are recommended. METHODS. The 1988 Child Health Supplement to the National Health Interview Survey collected 12-month recall information on injuries that occurred to a national sample of 17,110 children aged 0 through 17 years. Using information on timing of interviews and reported injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(178 citation statements)
references
References 5 publications
6
167
0
3
Order By: Relevance
“…As students who sustain injury during this time may continue school from next day after having overnight rest unless their injury is very severe; the consideration of 1-day limitation criteria can exclude such injuries. Moreover, only those injury episodes that occurred in the last 3 months preceding the survey were included by using a short recall period (1-3 months) as recommended by previous studies (Harel et al, 1994;Mock et al, 1999a). This recall period is particularly useful for measuring non-fatal injuries and reducing the recall bias.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…As students who sustain injury during this time may continue school from next day after having overnight rest unless their injury is very severe; the consideration of 1-day limitation criteria can exclude such injuries. Moreover, only those injury episodes that occurred in the last 3 months preceding the survey were included by using a short recall period (1-3 months) as recommended by previous studies (Harel et al, 1994;Mock et al, 1999a). This recall period is particularly useful for measuring non-fatal injuries and reducing the recall bias.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…Nor was there an attempt to obtain objective evidence of an illness event in the form of a residual deformity or debility. A 12-month recall period was used to produce higher frequencies of events for analyses, but had the drawback of possible memory decay (Harel et al 1994). To reduce recall bias, the inquiry was limited to specific illness events of serious import.…”
Section: Distribution Of Mortality ----------------------------------mentioning
confidence: 99%
“…Other studies were based on consequences of injuries, such as hospital admissions (Spady et al 2004) and visits to clinics (Hambridge et al 2002). Studies of the epidemiology of non-fatal injuries found that most non-fatal injuries result from recreational and sport activities and these occur mainly at school, home and in the neighbourhood (Harel et al 1994, Scheidt et al 1995, King et al 1996a, Harel 1998a. Each of these locations provides opportunities for intervention.…”
Section: Introductionmentioning
confidence: 99%